Catalyst free one-pot synthesis of α-aminophosphonates in aqueous ethyl lactate. (27th May 2019) - Gao, Ge; Chen, Meng-Nan; Mo, Li-Ping; Zhang, Zhan-Hui
Abstract: An highly efficient and environmentally friendly process for the synthesis of α-aminophosphonates has been devised, through a one-pot three-component condensation of various aldehydes, amines and triethyl phosphate in water-ethyl lactate under ultrasonic irradiation conditions at room temperature. The expected products were obtained in high yield without the need for any additional catalyst. Graphical Abstract: UF0001